Emergency Management of Unexpected Life-Threatening Septic Shock in a Patient Undergoing Ureteroscopic Stone Removal: A Case Report - Nihar Ranjan Tripathy; Sabyasachi Tripathy (New Frontiers in Medicine and Medical Research Vol. 15, 2021)
We present a case of life-threatening septic shock undergoing ureteroscopic stone removal in the operation theatre just after the surgery. Patient was symptomatically diagnosed on the operation table and intensively managed to stabilize quickly without wasting time and later it was confirmed by investigations that it was a septic shock resulted due to Gram negative bacilli E. coli. There have been very few cases reported in the literature.